Effect of Depth of Total Intravenous General Anesthesia on Intraoperative Electrically Evoked Compound Action Potentials in Cochlear Implantation Surgery - Ala”a Alhowary; Abdelwahab Aleshawi; Obada Alali; Manal Kassab; Diab Bani Hani; Khaled EL-Radaideh; Firas Alzoubi (Anesthesiology Research and Practice)
Purpose. This study aims to compare the effect of the depth of total intravenous anesthesia (TIVA) on intraoperative electrically evoked compound action potential (e-ECAP) thresholds in cochlear implant operations. Methods. Prospectively, a total of 39 patients aged between 1 and 48 years who were scheduled to undergo cochlear implantation surgeries were enrolled in this study. Every patient received both light and deep TIVA during the cochlear implant surgery. The e-ECAP thresholds were obtained during the light and deep TIVA. Results. After comparing the e-ECAP means for each electrode (lead) between the light and deep anesthesia, no significant differences were detected between the light and deep anesthesia. Conclusion. The depth of TIVA may have no significant influence on the e-ECAP thresholds as there was no statistical difference between the light and deep anesthesia.